Relentless placoid chorioretinitis: A review of four cases in pediatric and young adult patients with a discussion of therapeutic strategies - Zaheer, Haniah A.; Odden, Jamie; Gagrani, Meghal; Zaguia, Fatma; Lowder, Careen; Coca, Andreea; Rosenkranz, Margalit E.; Patil-Chhablani, Preeti; Ores, Raphaelle; Boussion, Francois; Indermill, Chad; Sahel, José-Alain; et al. (Frontiers in Pediatrics, 2023)
Introduction Relentless Placoid Chorioretinitis (RPC) is a rare, bilateral disease of the retinal pigment epithelium. The clinical course is prolonged and relapsing. No standard treatment has been established to date. The purpose of this case series is to report 4 cases of RPC in pediatric and young adult patients in which varying treatments were used, comparing them to previously published cases. Methods A multicenter retrospective chart review was done on 4 consecutive patients. These patients were diagnosed with RPC because of new chorioretinitis lesions continuing to appear without or despite therapy for 5 to 36 months (2 patients), with a clinical course prolonged and relapsing and/or because of the atypical location of the multiple lesions (>50) extending from the posterior pole to the equator and mid peripheral retina (all 4 patients), which were not consistent with other entities like acute posterior multifocal placoid pigment epitheliopathy and serpiginous choroiditis. Results All four cases of RPC, received oral and/or IV steroids acutely, and three of those patients were transitioned to a steroid sparing agent and biologic therapies: anti-TNF alpha or anti-IL-6. Quiescence of the chorioretinitis lesions was obtained after 7 months, 1 month and 36 months however, the latter had issues with treatment adherence. Mycophenolate mofetil was insufficient to control the disease in one patient but tocilizumab and infliximab thereafter were effective after cessation of adalimumab due to side effects. Adalimumab when started the first month after presentation was effective in controlling the disease in one patient. After failure of interferon-alpha-2a, one patient displayed long-term control with infliximab. One patient did not go on to require steroid sparing agent after oral prednisone taper as there was no evidence of progression or recurrence. Conclusion This case series adds to the current knowledge regarding potential treatments for RPC, specifically the use of anti-TNF alpha treatments and anti-IL-6, tocilizumab. In this case study, relapses of RPC were found among patients on mycophenolate mofetil and interferon-alpha-2a and one case did not relapse on oral steroids without steroids sparing agent. Our findings suggest that adalimumab, infliximab and tocilizumab may be useful medications to obtain quiescence of RPC.